Interfacial 2D Montmorillonite Nanocoatings Enable Sandwiched Polymer Nanocomposites to Exhibit Ultrahigh Capacitive Energy Storage Performance at Elevated Temperatures. Issue 35 (30th October 2022) - Wang, Yifei; Li, Zongze; Moran, Thomas J.; Ortiz, Luis A.; Wu, Chao; Konstantinou, Antigoni C.; Nguyen, Hiep; Zhou, Jierui; Huo, Jindong; Davis‐Amendola, Kerry; Zhou, Peinan; Huey, Bryan D.; et al.
Abstract: Polymer dielectrics are essential for advanced electrical and electronic power systems due to their ultrafast charge–discharge rate. However, a long‐standing challenge is to maintain their dielectric performance at high temperatures. Here, a layered barium titanate/polyamideimide nanocomposite reinforced with rationally designed interfaces is reported for high‐temperature high‐energy‐density dielectrics. Nanocoatings composed of 2D montmorillonite nanosheets with anisotropic conductivities are interposed at two kinds of macroscopic interfaces: 1) the interfaces between adjacent layers in the nanocomposites (inside) and 2) the interfaces between the surface of the nanocomposite and the electrode (outside). By revealing the charge transport behavior with Kelvin probe force microscope, surface potential decay, and finite element simulation, it is demonstrated that the outside nanocoatings are observed to diminish charge injection from the electrode, while the inside nanocoatings can suppress the kinetic energy of hot carriers by redirecting their transport. In this interface‐reinforced nanocomposite, an ultrahigh energy density of 2.48 J cm −3, as well as a remarkable charge–discharge efficiency >80%, is achieved at 200 °C, six times higher than that of the nanocomposite without interfacial nanocoatings. This research unveils a novel approach for the structural design of polymer nanocomposites based on engineered interfaces to achieve high‐efficient and high‐temperature capacitive energy storage. Abstract : Layered polymer nanocomposites incorporating 2D montmorillonite nanocoatings at interfaces achieve significantly enhanced dielectric energy storage and breakdown performance. The outside nanocoatings are effective at blocking charge injection, while the inside ones redirect penetrating charges to dissipate in‐plane instead.